إعادة توظيف العناصر التراثية بأساليب حديثة في تصميم الديكور الداخلي لتعزيز الهوية الثقافية (Al-Farooq Journal of Sciences, 2026)
This study aims to explore the re-employment of heritage elements in modern interior design and their role in strengthening cultural identity. It analyzes the relationship between various heritage values ​​(temporal, symbolic, architectural, urban, social, and local) and their integration into contemporary interior designs to achieve a balance between authenticity and modernity. The study employs a descriptive-analytical approach, utilizing inductive reasoning to review previous studies. Research tools include questionnaires, design model analysis, and scientific observation, drawing on diverse primary and secondary sources. The study was conducted on a sample of interior designers, faculty members, and users. The results show a high rate of incorporation of heritage elements in interior design, particularly in promoting cultural identity, belonging, and aesthetic appeal, while achieving a notable balance between heritage and contemporary trends. Furthermore, the study demonstrates that the thoughtful use of heritage elements contributes to enhancing the aesthetic and functional value of interior spaces and strengthening the sense of national identity. The study recommended the need to promote the integration of heritage into interior design, develop innovative methods for reinterpreting it using modern technologies, and support academic and applied programs that link cultural identity with contemporary design.
Keywords: employment practices, heritage elements, interior design, interior decoration, modern design styles, cultural identity, architectural heritage